The magnetic properties of Fe-Al-Nb intermetallic compounds - Imaizumi, M. [UNESP]; Laks, B.; Bejerano, J. M.Z.; Gama, S.; Coelho, A. A.; Mota, M. A.; Caram, R. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
The Fe2Nb intermetallic compound crystallizes in the MgZn2 structure ( hexagonal Laves phases) and its magnetic properties was studied extensively. We have simulated the Fe-Al-Nb alloys by the Fe substitution for Al atoms in the (0,0,0) and (0,0,0.5) sites of the Fe2Nb phase, and its magnetic behavior was studied using the linearized augmented plane waves (LAPW) method, code Wien (97). The spin magnetic moments are 1.53 μB for the Fe atom in the site with 6 Fe neighbors, -0.012 μB for the Al atom with 2 Al neighbors and -0.048 μB for the Nb atom with 4 Nb neighbors. In the metal, the spin magnetic moment is 2.31 μB for the iron atom. The authors show the magnetic behavior of the material by the change observed in the total density of states of spins up and spins down, and a magnetic moment measurement of this compound.